1983
DOI: 10.1111/j.1476-5381.1983.tb10529.x
|View full text |Cite
|
Sign up to set email alerts
|

Homotaurine: a GABAB antagonist in guinea‐pig ileum

Abstract: Homotaurine (3‐aminopropane sulphonic acid) did not inhibit the twitch response in guinea‐pig ileum longitudinal muscle whilst γ‐aminobutyric acid (GABA) and (−)‐baclofen evoked dose‐dependent inhibitions. The inhibitory effects of GABA and (−)‐baclofen were prevented in the presence of homotaurine 2 × 10−4 and 10−3 M. The log dose‐effect curves of GABA and (−)‐baclofen were shifted in a parallel manner compatible with competitive antagonism. The pA2 of homotaurine with GABA (4.22 ± 0.05) and (−)‐baclofen (4.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Since tetrodotoxin (3 x 10-7M) and hyoscine (10-7M) completely prevented L-Glu-induced contraction of the preparation, it appears that cholinergic neurones of the myenteric plexus are necessary for L-Glu-induced contractions of the ileum. It has previously been shown that GABAA-and GABAB-receptors are directly present on the cholinergic neurones of the myenteric plexus (Giotti et al, 1983;Cherubini & North, 1984). The possibility therefore exists that L-Glu receptors are also located on the cholinergic neurones.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since tetrodotoxin (3 x 10-7M) and hyoscine (10-7M) completely prevented L-Glu-induced contraction of the preparation, it appears that cholinergic neurones of the myenteric plexus are necessary for L-Glu-induced contractions of the ileum. It has previously been shown that GABAA-and GABAB-receptors are directly present on the cholinergic neurones of the myenteric plexus (Giotti et al, 1983;Cherubini & North, 1984). The possibility therefore exists that L-Glu receptors are also located on the cholinergic neurones.…”
Section: Discussionmentioning
confidence: 98%
“…The longitudinal muscle of their ilea with the myenteric plexus attached was prepared according to Paton & Zar (1968) with minor modifications (Giotti et al, 1983). Strips, about 3cm in length, weighing approximately 20mg, were prepared from the terminal portion of the ileum and placed in a modified Krebs solution of the following composition (mM): NaCI 135, CaCl2 2.4, KH2PO4 1.3, NaHCO3 16.3 and glucose 7.7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results pinpointed that while phosphonate (3) and sulfonate (2) moieties interacted well with the binding site of the enzyme, the carboxylic group (1) did not yield a strong interaction. Phosponate and sulfonate were exploited as carboxylate mimics of GABAergic agonists, such as g-amino butyric acid (4, GABA) and baclofen (7) [23][24][25][26]. Strikingly, these replacements shifted the pharmacological profiles of the resulting compounds to GABAergic antagonists (5,6,8,9).…”
Section: Introductionmentioning
confidence: 98%
“…maximal inhibition=49 AE 8%; Àlog IC 50 =5.65 AE 0.14), as previously reported. 26 This effect on GABA B receptors subtypes was competitively antagonized by the selective GABA B blocker CGP-52432 (pK B =6.56 AE 0.10) and not competitively by compound 1 pD 0 2 ¼ 5:59 AE 0:16. Compounds 2 and 2a were completely ineffective in this test at concentrations up to 100 mM.…”
Section: In Vitro Testsmentioning
confidence: 97%